Hoax and Paradox of Digital Public Sphere - Wisnu Prasetya Utomo (Jurnal Komunikasi Indonesia, 2022)
Along with technological development, social media have brought various problems which have not been thought of before. Various public conversations are mediated in a space which initially was idealised as an equal and free space. However, multiple indicators indicate that the digital public sphere is vulnerable to hoaxes and fake news. This essay discusses the rise of hoax spreading groups in Indonesia and applied several cases to look back at the public sphere concept in the digital era.